Analysis of hydromagnetic micropolar nanofluid flow past a nonlinear stretchable sheet and entropy generation with Navier slips. (4th May 2022) - Fatunmbi, Ephesus Olusoji; Salawu, Sulyman O.
ABSTRACT: The study numerically investigates the model of hydromagnetic, dissipative micropolar nanofluid flow being influenced by multiple slips and mass flux. Also, the entropy generated within the conducting chemical reactive micropolar nanofluid is examined in permeable media. Thermophoretic and Brownian motion impacts are examined on the model. The flow is assumed to be two-dimensional over a flat nonlinear stretchable sheet in a saturated porous medium of non-Darcy type. Mathematical equations representing the problem are converted from partial to ordinary differential equations by similarity transformation. The dimensionless form of the equations is solved using a shooting technique associated with Runge-Kutta algorithms of order four. The outcomes of the simulation are displayed graphically while comparisons are made with reported data in the literature for some limiting situations. The results reveal that the momentum boundary layer is enhanced with rising values of the Brownian motion term whereas a decrease in the concentration distribution is found with a rise in Brownian motion. Besides, the thermophoresis parameter reduces entropy production in the system and the Bejan number is also reduced.